The application of Wasatiyyah in the Islamic insurance industry (Takaful) - Che Mohd Salleh, Marhanum (LEGAS, 2014)
The success of Prophet Muhammad (pbuh) in doing business while spreading Islam all over the world is acknowledged. The secret behind his success is the practice of Wasatiyyah throughout his life including business activities. In this instance, the practice of Wasatiyyah had united the Muslims without differentiation between races or country in the world. Moreover, the uniqueness of this concept has also attracted non-Muslims to learn the Islamic business as implemented by the Prophet Muhammad (pbuh). In this respect, the concept of Islamic insurance currently known as Takaful was implemented during the Prophet’s time and it achieved success. The success of the Islamic insurance is due to the concept applied, which promoted the spirit of brotherhood and Wasatiyyah among the society, where the life of everybody is under protection. Wasatiyyah in this context is defined as fairness and an equal balance of the benefits received by society where the objective is to generate a better society in the future. This article discusses in details the concept of Wasatiyyah or fairness that has been applied in the current Islamic insurance industry in terms of the Islamic principles applied in the Takaful products and also the aspect of marketing that should be practiced in the industry. It is necessary to promote the concept of Wasatiyyah in the Takaful industry as it may act as an agent of unity among the Muslims and at the same time promote Islam to the world.